A Novel Interval Type-2 Fuzzy Logic Controller for Shunt Active Power Filters in Power Quality Enhancement - Sidik, Aryo De Wibowo Muhammad; Efendi, Efendi; Lumbantobing, Harurikson; Indrawan, Bayu; Junfithrana, Anggy Pradiftha; Ula, Rini Khamimatul; Suryana, Anang; Tambunan, Handrea Bernando; Narputro, Panji; Artiyasa, Marina (Fidelity : Jurnal Teknik Elektro, 2024)
This paper proposes a novel control strategy for enhancing power quality through the implementation of an Interval Type-2 Fuzzy Logic Controller (T2FLC) for Shunt Active Power Filters (SAPF). The presented method effectively addresses harmonic distortions introduced by non-linear loads, a common issue in modern electrical systems. Extensive simulations conducted in MATLAB/Simulink demonstrate the T2FLC's ability to regulate the DC bus voltage while significantly reducing Total Harmonic Distortion (THD). The method achieves superior performance compared to both traditional passive and active filtering techniques, reducing THD within the limits specified by IEEE 519-2014 standards. The results confirm the robustness and adaptability of the proposed approach across varying load conditions, establishing it as a reliable and scalable solution for improving power quality in complex electrical networks.